Solid Phase-Based Microextraction Techniques in Therapeutic Drug Monitoring - Sofia Soares; Tiago Rosado; Mário Barroso; Eugenia Gallardo (MDPI AG, 2023)
Therapeutic drug monitoring is an established practice for a small group of drugs, particularly those presenting narrow therapeutic windows, for which there is a direct relationship between concentration and pharmacological effects at the site of action. Drug concentrations in biological fluids are used, in addition to other clinical observation measures, to assess the patient's status, since they are the support for therapy individualization and allow assessing adherence to therapy. Monitoring these drug classes is of great importance, as it minimizes the risk of medical interactions, as well as toxic effects. In addition, the quantification of these drugs through routine toxicological tests and the development of new monitoring methodologies are extremely relevant for public health and for the well-being of the patient, and it has implications in clinical and forensic situations. In this sense, the use of new extraction procedures that employ smaller volumes of sample and organic solvents, therefore considered miniaturized and green techniques, is of great interest in this field. From these, the use of fabric-phase extractions seems appealing. Noteworthy is the fact that SPME, which was the first of these miniaturized approaches to be used in the early '90s, is still the most used solventless procedure, providing solid and sound results. The main goal of this paper is to perform a critical review of sample preparation techniques based on solid-phase microextraction for drug detection in therapeutic monitoring situations.